Juridical Review Article 27 Paragraph (1) of the Law of the Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions against the Crime of Online Prostitution in Indonesia (JURNAL HUKUM SEHASEN, 2020)
Law of the Republic of Indonesia Number 11 of 2008 concerning Electronic Information and Transactions, so far Article 27 Paragraph (1) cannot ensnare all perpetrators involved in online prostitution crimes, such as service users, service providers, pimps, against these actions. different actions, the problem is against the perpetrators of online prostitution, applied with different articles and there are the same, namely Article 27 paragraph (1) UUITE and Article 296 of the Criminal Code. There should be clearer regulations to regulate online prostitution. The formulation of the problem is how to review the law of Article 27 Paragraph (1) of the Law of the Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions against online prostitution crimes. How is the judge's consideration in giving a decision on online prostitution related to the application of Article. 27 Paragraph (1) of the ITE Law on online prostitution in Indonesia. The theory used is the theory of law enforcement and the theory of punishment, this type of research is normative legal research. The data obtained is from the data of district court decisions on cases of online prostitution, there are two decisions of online prostitution cases and the application of different articles.